102: EFFECT OF A MULTIMODAL PREHABILITATION PROGRAM ON POSTOPERATIVE RECOVERY AND MORBIDITY IN PATIENTS UNDERGOING A MINIMALLY INVASIVE ESOPHAGECTOMY. (23rd April 2022) - Janssen, H; Fransen, L; Heesakkers, F; Dolmans-Zwartjes, A; Moorthy, K; Nieuwenhuijzen, G; Luyer, M
Abstract: Background and aim: Despite recent advancements in perioperative care, postoperative morbidity following an esophagectomy remains substantial. Studies in other major abdominal surgery, have shown that prehabilitation can improve short-term outcomes. This single-center cohort study investigated the effect of prehabilitation in patients undergoing minimally invasive Ivor-Lewis esophagectomy (MIE-IL). Methods: Data were collected on consecutive patients receiving a standardized ERAS program that included direct start of oral feeding following MIE-IL (from postoperative day one), between October 2015 and February 2020. The intervention group comprised patients enrolled in the PREPARE prehabilitation program that was implemented in 2018 as the standard care pathway for all patients. The control group comprised a retrospective cohort prior to implementation of PREPARE. Postoperative outcomes included (functional) recovery, length of hospital stay (LOHS), cardiopulmonary complications (CPC) and other predefined outcomes. Results: The PREPARE group comprised 52 patients and control group 43 patients. Median time to functional recovery was 6 vs. 7 days ( P = 0.074) and LOHS 7 vs. 8 days ( P = 0.039) in the PREPARE and control group, respectively. Hospital readmission rate was 9.6% vs. 14.3% ( P = 0.484). Although thirty-day overall postoperative complication rate did not differ statistically significantly ( P = 0.106), a clinically relevant reduction of 17% was observed in PREPARE patients. Similarly, CPC rate was 14% lower in the PREPARE group ( P = 0.190). Anastomotic leakage rate was similar (9.6% vs 14.0%; P = 0.511). Despite no difference in severity (Clavien-Dindo) of complications ( P = 0.311), ICU readmission rate was lower in PREPARE patients (3.8% vs. 16.3%, P = 0.039). In the PREPARE group wherein maximum oxygen uptake capacity (VO2max) was assessed preoperatively during a Steep Ramp Test, VO2max was lower at baseline in patients diagnosed with postoperative complications ( P = 0.011). There were no data on VO2max in the control group. Conclusion: Prehabilitating patients prior to a MIE-IL led to a shorter LOHS and reduced ICU readmission rate. Additionally, a clinically relevant improvement in (functional) recovery and reduction in postoperative morbidity was observed in patients that were prehabilitated.